Assessment – Instructions: Intelligence Reports and Handing over notes 1932-1948 (Source: NAC Buea; Collector: OGE; Date: 2021) (Colonial Letters and the Contact of Knowledges, 1932)
This file contains colonial assessment report, instructions and handing over notes 1932-1948
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Colonial Native Court; Colonial Instructions; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies